Quand l'art prend la rue - Bilodeau, Maxime (Continuité, 2024)
issued: 2024-23-00
Keywords: Monuments; Places publiques

PHILLIPS, MARY MARTHA - McLeod, Ellen Easton (Dictionnaire biographique du Canada, 2023)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman; William; Photographie; Publicité

CULLEN, MAURICE GALBRAITH - Prioul, Didier (Dictionnaire biographique du Canada, 2022)

Photography: Science, Technology, and Practice in Nineteenth-Century Canada - Schwartz, Joan M. (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Astronomie; Géologie; Notman; William; Photographie

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman; William; Photographie; Écossais

Women in Westmount (The Westmount Historian, 2020)
Number: 2
Keywords: Femmes; Peinture; Élections

CARLI, ALEXANDRE - Carlevaris, Anna Maria (Dictionnaire biographique du Canada, 2020)

Le champ des décors polychromes dans les églises au Québec entre 1850 et 1930 - Bellerose, Véronique (Université du Québec à Montréal, 2019)
Keywords: Arts sacrés; Bourassa; Napoléon; Leduc; Ozias; Peinture; Églises

L'art de la gravure entre 1850 et 1885 et l'architecture commerciale de Montréal : le cas de John Henry Walker - Sirois, Hélène (Université du Québec à Montréal, 2019)
Keywords: Gravure; Publicité; Walker; John Henry

HAMMOND, JOHN - Tisdale, Jane (Dictionnaire biographique du Canada, 2019)

Reinforcing racial hierarchy through visual culture : black enslaved children in New France and early Quebec (1700-1834) - Trahan-Thomassin, Marilou (Université McGill, 2019)
Keywords: Enfants; Esclaves; Noirs; Peinture; Publicité

Envisioning new futures: Portrait photographs of black Victorians in Montreal, 1861-1901 - Evoughlian, Sandra (Université McGill, 2018)
Keywords: Noirs; Notman; William; Photographie

Frankenstein’s Tory: Graphic Satire in 1840s Montreal, from Le Charivari canadien to Punch in Canada - Hardy, Dominic (McGill-Queen's University Press, 2018)
Keywords: Caricature; Humour

Sketches from An Unquiet Country - Hardy, Dominic; Gérin, Annie; Senechal Carney, Lora (McGill-Queen's University Press, 2018)
Keywords: Bourgeois; Albéric; Caricature; Humour; Idéologies; Julien; Henri; Walker; John Henry

Uncle Sam, A Not-So-Distant Cousin: Canadian Contributions to the Genesis of a US Allegorical Figure - Vachon, Christian (Sketches from An Unquiet Country, 2018)
Keywords: Caricature; Julien; Henri; Walker; John Henry

L’ancien square Dominion à Montréal: un parcours d’art et d’histoire - Joly, Diane (Histoire Québec, 2017)
Number: 4
Keywords: Dominion (square); Idéologies; Monuments; Places publiques; Squares

Entre passion et raison : une histoire du collectionnement privé à Montréal (1850-1910) - Truchon, Caroline (Université de Montréal, 2017)
Keywords: Expositions; Musées

La vie et l'oeuvre de Maurice Day, artiste visuel pointelier - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2016)

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

The Likeness of Fugitivity: William Notman's Carte-de-visite Portrait of John Anderson - Boone, Emilie (History of Photography, 2013)
Number: 2
Keywords: Notman; William; Photographie

L'iconographie d'une littérature: évolution et singularités du livre illustré francophone au Québec, 1840-1940 - Danaux, Stéphanie (Presses de l'Université Laval, 2013)
Keywords: Édition

Sulpician Cultural Strategies: The Fine Arts - Des Rochers, Jacques (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46706
Keywords: Communautés religieuses; Sulpiciens

Dessins de voyage - Drouin, Daniel (Continuité, 2013)
issued: 2013-23-00

William Notman et les imaginaires photographiques de la chasse au XIXe siècle à Montréal - Lahaie, Andréann (Université du Québec à Montréal, 2013)
Keywords: Notman; William; Photographie

La bourgeoisie en portrait au Bas-Canada (1790-1830) - Bernier, Geneviève (Université Laval, 2012)
Keywords: Bourgeoisie; Peinture

The Surrender of Montreal to General Amherst de Francis Hayman et l'identité impériale britannique - Turcot, Laurent (Mens, 2011)
issued: 2011-23-00
Keywords: Capitulation; Guerre; Peinture

Ressemblance et caractère dans les portraits de Théophile Hamel (1840-1870) - Aubé-Gaudreau, Adrienne (Université Laval, 2010)
Keywords: Peinture

Napoléon Bourassa et la vie culturelle à Montréal au XIXe siècle - Vallée, Anne-Élisabeth (Leméac, 2010)
Keywords: Art association; Bourassa; Napoléon; Peinture; Sculpture; École des Beaux-Arts

Un héritage méconnu: les tableaux de l'ancienne église Notre-Dame de Montréal - Des Rochers, Jacques (Éditions de la Fabrique de la paroisse Notre-Dame de Montréal, 2009)
Keywords: Arts sacrés; Notre-Dame (église); Peinture; Églises

L'iconographie rébellienne, la face cachée de l'historiographie des rébellions de 1837-1838: quelques études de cas - St-Jean, France (Mens, 2009)
issued: 2009-23-00
Keywords: Histoire; Rébellions

La contribution artistique, pédagogique et théorique de Napoléon Bourassa à la vie culturelle montréalaise entre 1855 et 1890 - Vallée, Anne-Élisabeth (Université du Québec à Montréal, 2009)
Keywords: Art association; Bourassa; Napoléon; Peinture; Sculpture; École des Beaux-Arts

The Pictured and the Posed: Nineteenth Century Touristic Images of the Lachine Rapids - Eagan, Mireille M. (Université Concordia, 2008)
Keywords: Lachine; Paysages; Peinture; Photographie; Tourisme

Design, Presentation Silver and Louis-Victor Fréret (1801-1879) in London and Montreal - Fox, Ross (Material Culture Review / Revue de la culture matérielle, 2008)
Pas dans la période V car il n'est pas à Montréal avant 1867 de ce que nous (JRL) comprenons
issued: 2008-21-00
Keywords: Artisans; Sculpture

Théophile Hamel: peintre (1817-1870) - Hamel-Beaudoin, Françoise (Lidec, 2008)
Keywords: Peinture

Construction de la valeur de l'objet d'art dans les monographies paroissiales au Québec de 1854 à 1925 - Miglioli, Nathalie (Patrimoine et sacralisation, 2008)
Keywords: Arts sacrés; Églises

Stratégies culturelles sulpiciennes: les beaux-arts - Des Rochers, Jacques (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Les Sulpiciens au Canada - Dickinson, John A.; Da Silva-Gauthier, Angélique (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

A City's Museum: A History of the Montreal Museum of Fine Arts - Germain, Georges-Hébert (Musée des Beaux-arts de Montréal, 2007)
Translators: _:n56618 Translators: _:n57240
Keywords: Art association; Musée des Beaux-Arts; Musées

Un musée dans la ville. Une histoire du Musée des Beaux-arts de Montréal - Germain, Georges-Hébert (Musée des Beaux-arts de Montréal, 2007)
Keywords: Art association; Musée des Beaux-Arts; Musées

Pastorale et prédication - Rousseau, Louis (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Sulpiciens

Les photographes québécois: la première liste officielle (1839-1950) - Allard, Jean-Luc; Poitras, Jacques (Éditions historiques et généalogiques Pépin, 2006)
Keywords: Photographie

La nature morte au Québec et la question du sujet en art (1887-1907) - D'Amours, Annie (Université Laval, 2005)
Keywords: Peinture

TOPLEY, WILLIAM JAMES - Rodger, Andrew (Dictionnaire biographique du Canada, 2005)

L'histoire par l'image: commémoration picturale, pouvoir politique et stratégies visuelles au Québec (1880-1930) - Roy, Nathalie Anne (Université McGill, 2005)

Les trésors de l'atelier pointelier de Urbain Brien dit Desrochers (1781-1860), sculpteur ornemaniste - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2004)
Keywords: Arts sacrés; Sculpture

After Notman: Montreal Views - A Century Apart / D'après Notman: Regards sur Montreal - Un siècle plus tard - Maciejewski, Andrzej (Firefly Books, 2003)
Translators: _:n46500
Keywords: Notman; William; Photographie

L'implantation de la galerie d'art à Montréal: le cas de W. Scott & sons, 1859-1914. Comment la révision du concept d'œuvre d'art autorisa la spécialisation du commerce d'art - Sicotte, Hélène (Université du Québec à Montréal, 2003)
Keywords: Expositions; Peinture

Louis-Philippe Hébert, 1850-1917. Sculpteur national - Hébert, Bruno (Lidec, 2002)
Keywords: Arts sacrés; Hébert; Philippe; Monuments; Sculpture

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith; Donald

Un album du mont Royal (Continuité, 2001)
issued: 2001-23-00
Keywords: Mont Royal